Efficient Use of Graphene Oxide and Silica Fume in Cement-Based Composites - Ahmad Abdullah (MDPI AG, 2021)
Incorporation of graphene oxide (GO) and silica fume (SF) to cement composites enhances their mechanical properties if suitable proportional amounts of GO and SF are used. This study presents a simplified approach to determine experimentally the optimum GO and SF contents that should be added to the cementitious mixture to obtain a proper and stable dispersion of GO sheets within the cement matrix. Composite mortar specimens with different GO and SF contents were designed and tested under flexural and compression loading. The phase formation and the microstructure of selected samples were also investigated to give an in-depth interpretation of the test results. The main criterion to determine the GO and SF contents was the ultimate strength required of the GO–cement composite. It was found that there was a composite interaction between the SF and GO contents in the cementitious mixture, which an envelope surface could describe if all other mix design parameters are kept constant.